Dr. Achih H. Chen — Deep Plane Facelift — Augusta - Chen, Achih H. (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Achih H. Chen, practicing in Augusta, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003279; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; augusta